ANALISIS SEMIOTIKA DALAM NARASI MICROFICTION DI AKUN INSTAGRAM FIKSIMINI.ID: TEORI SEMIOTIKA ROLAND BARTHES - Andi Fakhirah; Nur Indah; Abdul Haliq (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This study aims to analyze microfiction published on the Instagram account Fiksimini.id using Roland Barthes' semiotic theory approach. Microfiction, as a form of modern literary work with a limited number of words, stores complex meanings through symbols and signs. This study identifies the denotative, connotative, and mythical meanings contained in microfiction to understand how this narrative reflects social, political, and cultural realities. The research method used is qualitative descriptive, with data collection techniques through observation, documentation, and content analysis. The results of the analysis show that microfiction on Fiksimini.id not only conveys messages directly, but also contains in-depth social criticism of various contemporary issues. This study is expected to contribute to the development of semiotic studies and understanding of microfiction as a medium for representing ideology in literary communication.